Effects of Interpersonal Trust on Employee Avoidance and Approach Self-regulation - Bigley, Gregory A. (Institutional Knowledge at Singapore Management University, 2009)
We maintain that two forms of interpersonal trust predict different work behaviors because they tap different psychological systems of self-regulation. We contend also that the two trust forms interact as a function of the ambivalence they jointly produce. Our model was confirmed in a large sample of engineers employed by a Fortune 500 company. Our study extends prior research that presumes an employee integrates all the positive and negative information possessed about another into a single summary trust statistic and then behaves accordingly.